Does Corporate Citizenship Have Gender? - Verdu Sanmartin Amalia (Routledge, 2022)
Corporate citizenship is an area of growing interest in the study of the social responsibilities of business. This chapter considers the role of gender within corporate citizenship arena and posits that the historical definition of the ‘citizen’ as male influence our current thinking around constructs of corporate citizenship. Feminist discourse on gender has affected the policies and laws that rule corporations and society in general to some extent, but the importance of gender within the corporation interplays with these discourses and the role of the corporation in social change.
Corporate Citizenship and Family Business